Complete Control of Multichannel, Angle‐Multiplexed, and Arbitrary Spatially Varying Polarization Fields. Issue 6 (14th January 2020) - Wang, Enliang; Niu, Jiebin; Liang, Yonghao; Li, HaiLiang; Hua, Yilei; Shi, Lina; Xie, Changqing
Abstract: In recent years, much effort is dedicated to the generation of vectorial optical fields with an arbitrary spatially varying polarization distribution by means of metasurfaces. However, simultaneous and independent control of the amplitude, phase, and polarization is still challenging, especially for the multichannel generation of a vectorial optical field with an angle‐multiplexed functionality. Here, a facile route, called coherent pixel polarization metaholography, is proposed to realize multichannel, angle‐multiplexed, and arbitrary spatially varying polarization fields and demonstrate how to enable a fully independent realization of full Poincaré beams (lemon, start, spider, and web beams), dual‐way switching print images, vectorial print images, and optical polarization knot profiles. Importantly, the demonstrated angle‐multiplexed metasurfaces have an independently controllable handedness and azimuth and can possess up to four channels. Such angle‐multiplexed multichannel arbitrary spatial polarization fields may enable various applications, including optical dynamic displays, information communication, optical encryption, and quantum experiments. Abstract : Coherent pixel polarization metaholography is proposed to realize multichannel, angle‐multiplexed, and arbitrary spatially varying polarization fields. Full Poincaré beams (lemon, start, spider, and web beams), dual‐way switching print images, vectorial print images, and optical polarization knot profiles are experimentally realized. Additionally, the demonstrated angle‐multiplexed metasurfaces have an independently controllable handedness and azimuth and allow up to four channels.